Penilaian Kinerja Bank Syariah Menggunakan Pendekatan Maqashid Syariah Indeks Periode Tahun 2018-2020 - Nur Faizah; Riana Alvita R (Department of Islamic Banking, 2021)
The aim of the study is to determine the performance of Islamic Bankand how to compare the performance of Islamic Bankin Indonesia in 2018-2020 as measured by the maqashid sharia index. This research includes descriptive quantitative research, with the research object of four Islamic banks, namely Bank Negara Indonesia Syariah, Bank Rakyat Indonesia Syariah, Bank Syariah Mandiri, and Bank Muamalat Indonesia. The data used are the 2018-2020 annual financial reports obtained from the official websites of each bank. The method used is the Maqashid Syariah Index (MSI) and the data analysis technique uses SAW (Simple Attribute Decision Making). The results of the study are (1) the performance of Islamic Bankfor three years has fluctuated. However, (2) each Islamic Bank has its own advantages from each objective of the Maqashid Syariah Index, as well as, there are Bankthat are incomplete in providing the information needed to conduct a performance assessment.